2015
DOI: 10.1007/s12672-015-0226-1
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Control Trial Comparing the Efficacy of Antiandrogen Monotherapy: Flutamide vs. Bicalutamide

Abstract: The study aims to compare serial changes in prostate-specific antigen (PSA), testosterone, dehydroepiandrosterone (DHEA), and androstenedione in patients treated with either of the antiandrogen agents, bicalutamide or flutamide, using a randomized controlled study. Patients had to meet the following inclusion criteria: (1) presence of histopathologically confirmed prostate cancer, (2) prostate cancer treatment naive, (3) no current treatment with luteinizing hormone-releasing hormone (LH-RH) agonist for sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The declines on the third day are approximately 32% (the 2-week regimen) and 34% (the 1-h regimen), while on the 7th day, it was about 72% and 66%. The decrease in PSA on day 7 was consistent with 4 weeks of bicalutamide treatment ( 21 ), indicating a strong blocking effect of apalutamide. The half-life of PSA in human serum is approximately 3 days ( 27 , 28 ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The declines on the third day are approximately 32% (the 2-week regimen) and 34% (the 1-h regimen), while on the 7th day, it was about 72% and 66%. The decrease in PSA on day 7 was consistent with 4 weeks of bicalutamide treatment ( 21 ), indicating a strong blocking effect of apalutamide. The half-life of PSA in human serum is approximately 3 days ( 27 , 28 ).…”
Section: Discussionsupporting
confidence: 71%
“…The effect of single use of bicalutamide on endocrine in vivo has been reported: LH, FSH, testosterone and dihydrotestosterone all increased to varying degrees ( 20 ). After oral administration of flutamide and bicalutamide for 4 weeks ( 21 ), the testosterone level remained high, and the PSA level decreased by about 70%, which was comparable to that of apalutamide for 1 week ( Supplementary Table 1 ), suggesting that the time can be shortened when apalutamide is used to prevent the flare-up effect of GnRH agonist. Taking into account the half-life of PSA (about 3 days), newly generated PSA in the third day is only about 16% of the original ( Supplementary Figure 1 ), lower than administration of flutamide and bicalutamide for 4 weeks.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast to bicalutamide with no effect on adrenal androgen, flutamide was shown to significantly reduce the level of dehydroepiandrosterone (DHEA) in addition to androgen receptor blockade. [ 27 ] However, whether reduction in adrenal androgen contributes to fracture risk in patients with carcinoma of the prostate remains to be confirmed by further studies. ( Fig 2 )…”
Section: Discussionmentioning
confidence: 99%
“…② The level of DHEA has been shown to negatively predict the response to abiraterone for patients with CRPC [ 4 ]. ③ Flutamide after bicalutamide can be effective in lowering the level of DHEA [ 5 , 6 , 8 ]. Therefore, the response to flutamide as a second-line therapy after bicalutamide can predict the response to abiraterone.…”
Section: Main Textmentioning
confidence: 99%
“…Considering the mechanism of abiraterone, Kim et al [ 4 ] reported that the level of dehydroepiandrosterone (DHEA) was a good predictor of prostate-specific antigen (PSA) response in patients with CRPC who were treated with abiraterone, and that the level of DHEA in all patients was undetectable after 8 weeks of abiraterone treatment. In our previous randomized study, which compared the levels of DHEA in castration-sensitive prostate cancer patients who were treated with flutamide versus bicalutamide monotherapy, flutamide lowered DHEA levels, but bicalutamide did not [ 5 ]. Ayub et al [ 6 ] reported that flutamide decreased the serum level of DHEA sulfate by inhibiting the activity of CYP17.…”
Section: Introductionmentioning
confidence: 99%